Bridging Ends and Means: The Centrality of Targets in Comparative Policy Analysis with Illustrations in the United States, New Zealand, and Germany. Issue 5 (20th October 2018) - Merrill, Ryan; White, Lee
Abstract: Policy means are shaped not only by policy goals, but also by the groups of actors targeted through policies for change. Yet the importance of targets is not visible in current frameworks describing policy development. The article advances a modified version of Howlett and Cashore's nested model of policy instrument choice that makes explicit the centrality of targets as a bridging step between policy means and ends. It illustrates application of this target-centered framework for comparative policy analysis through three evaluations of transformative environmental policy regimes implemented in the United States, New Zealand, and Germany. Target-centered analysis provides insights into the development of each policy by separating out target and client selection from the goals and means of each policy, and shows how including targets as an explicit step in policy analysis clarifies and extends our understanding of both formulation and reform. In particular, distinguishing the calibration of policy mechanisms from the rules that define which entities are impacted by a given tool reveals patterns by which policymakers tailor interventions in the distribution of burdens and benefits to various social groups.